Alteration of Angiopoietin-Like Protein 4 Levels in Serum or Urine Correlate with Different Biochemical Markers in Hyperlipidemia-Related Proteinuria. (23rd March 2020) - Gao, Xia; Zhang, Min; Feng, Weidong; Xu, Zichuan; Wang, Yan; Shi, Lingna; Zhang, Jing
Abstract : Angiopoietin-like protein 4 (ANGPTL4) is widely known as a key regulator of lipid metabolism. We investigated the relationship between ANGPTL4 expression in serum or urine and blood lipid or urine protein levels of patients with hyperlipidemia- (HL-) related proteinuria. Sixty-eight patients with HL-related proteinuria (HL-Pro group), 68 patients with HL without proteinuria (HL-NPro group), 46 patients with non-HL-related proteinuria (NHL-Pro group), and 50 healthy control (Con) subjects were selected. There were no significant differences in serum ANGPTL4 levels between the Con group (36.82 ± 17.03  ng/ml) and the HL-Pro group (27.94 (18.90, 53.72) ng/ml). Additionally, the serum ANGPTL4 levels in the HL-Pro group were significantly lower than those in the HL-NPro group (53.32 ± 24.01  ng/ml) (P < 0.001 ). The urine ANGPTL4/Cr levels in the HL-Pro group (52.01 (45.25, 79.79) μ g/g) were significantly higher than those in the HL-NPro group (9.96 (8.35, 12.43) ng/ml) (P < 0.05 ). A significant alteration in urine ANGPTL4/Cr levels was observed in the NHL-Pro group (69.41 ± 55.36   μ g/g) and the Con group (10.08 ± 2.38   μ g/g) as well. There was no correlation between serum and urine ANGPTL4 levels of the four groups (P > 0.05 ). Serum ANGPTL4 levels (HL-Pro/HL-NPro group) were positively correlated with total cholesterol (TC) and triglyceride (TG) levels in hyperlipidemia patients. However, there was no correlation between urinary ANGPTL4 levels and TC or TG (P > 0.05 ). Urine ANGPTL4 levels were positively correlated with 24hUPro in patients with renal impairment (HL-Pro/NHL-Pro group). To summarize, ANGPTL4 may be considered an accurate predictor of proteinuria with HL. Notably, serum or urine ANGPTL4 levels indicated the degree of proteinuria or hyperlipidemia, respectively, in HL patients.